Perbandingan Motivasi Belajar Mahasiswa Laki-Laki dengan Mahasiswa Perempuan - Rahmadhania Rizanty; Ira Agus Sofiana; Dian Ekawati; Chasya Aghniarrahmah (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to examine the differences in learning motivation between male and female students in higher education. Learning motivation is a crucial factor that influences academic success. The research employed a quantitative approach with a descriptive comparative design. The sample consisted of 100 from University X in East Jakarta, comprising 50 males and 50 females selected through proportional random sampling. Data were collected using a Likert-scale questionnaire and analyzed using an independent t-test. The findings reveal a significant difference in learning motivation between female students (mean score = 94.84) and male students (mean score = 90.24) with a significance value of 0.014. These results indicate that female students tend to have higher learning motivation than male students. Contributing factors such as gender, learning environment, and psychological aspects are also discussed. This study is expected to serve as a reference for educators in developing learning strategies that can equally enhance students’ motivation regardless of gender.